The impact of Administrative Leadership on Job Satisfaction in Chadian Universities: An applied Study on King Faisal University of Chad and Hec-Tchad University Jun2020 - Hassan, Mahamat Boukhari; Tidjani, Atteib Hassan (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aims: to clarify the most important administrative leadership forms, identify the impact of leadership on the behavior of Universities’ staffs, demonstrate the extent to which lecturers’ educational performance is affected by the leadership of the university administration and to know the level of relationship between the leaders and lecturers. The study used the descriptive analytical method. The most important findings of the study are: Chadian universities’ leaders don’t take decisions based on the opinion on the majority, universities’ leaders don’t take decision based on the others opinions, universities’ administration don’t take in to account employees suggestions and decisions are not taken clearly and with transparency.
Keywords: impact; leadership; management; job satisfaction